2020
DOI: 10.1177/1559325820926764
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum Calcium Level Is Negatively Correlated With Systemic Lupus Erythematosus Activity

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease and hypocomplementemia signifies disease activity. Several studies have shown that calcium may help maintain optimum function of immune system and metabolism in SLE. The aim of our study was to analyze the relationship between total serum calcium level and SLE activity. A total of 66 patients with SLE and 214 healthy controls were included in this study. Our results showed lower serum levels of calcium ( P < .001), complement C3 ( P < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In a similar manner, the renal processing of phosphorus can modify its capacity in order to fulfil the requirements of cells for phosphorus. As confirm with previous study, patients with SLE had decreased serum calcium compared to healthy controls (93). The result showed that serum calcium reduced in mice lacking…”
Section: Chapter V Disscussionsupporting
confidence: 91%
“…In a similar manner, the renal processing of phosphorus can modify its capacity in order to fulfil the requirements of cells for phosphorus. As confirm with previous study, patients with SLE had decreased serum calcium compared to healthy controls (93). The result showed that serum calcium reduced in mice lacking…”
Section: Chapter V Disscussionsupporting
confidence: 91%
“…7 Besides, total blood calcium level is negatively correlated with systemic lupus erythematosus activity. 18 In this study, we found that postoperative bleeding decreased with increasing levels of blood calcium, implying that to some extent, blood calcium concentration levels may be associated with postoperative bleeding in cardiac surgery patients. We found there was a significant difference in blood albumin concentration preoperatively and patients with hypocalcemia have lower albumin levels.…”
Section: Discussionmentioning
confidence: 56%
“…Calcium levels may be more important in the SLE disease process than previously thought. Hypocalcemic events are more common in SLE patients [23]. As a result, changes in total serum calcium levels in our study SLE patients could have contributed to the drop in serum albumin level [23].…”
Section: Resultsmentioning
confidence: 64%